1982
DOI: 10.1007/bf02150095
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact specular microscopy of the normal corneal endothelium

Abstract: The corneal endothelium of 179 healthy persons (327 eyes), 4-89 years of age. as photographed through a non-contact specular microscope. From the histograms of the cell areas of each eye, other parameters were derived and subjected to computerized statistical analysis. In addition, photographs of both eyes of one person were taken on two different days and examined to determine the reproducibility of the method. The known age-dependent increase in the mean cell area as well as the decrease of the cell density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…There is now a large body of literature on the analysis of the cornea by specular microscopy, and this is widely accepted as a safe, well-reproducible, and reliable testing procedure [1,2,3,4,9,12,13,16,17]. An alternative to in vivo corneal analysis is confocal corneal microscopy, which has been introduced into routine clinical practice within the past 10 years [5,10,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…There is now a large body of literature on the analysis of the cornea by specular microscopy, and this is widely accepted as a safe, well-reproducible, and reliable testing procedure [1,2,3,4,9,12,13,16,17]. An alternative to in vivo corneal analysis is confocal corneal microscopy, which has been introduced into routine clinical practice within the past 10 years [5,10,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Confocal microscopes, which have several common design features with specular microscopes, have also been used to examine corneal endothelium, although their use has not been as common as specular microscopes. 13 Nidek recently introduced the ConfoScan 3, a confocal microscope that captures clear images of the corneal endothelium.…”
mentioning
confidence: 99%
“…In a particular study of 58 human corneas [38], the mean cell area measured was 334 ± 51 µm 2 (range: 273–553 µm 2 ), while in a separate study of 327 cornea endothelium [39], the mean cell area was reported to be 396 ± 132 µm 2 (range: 157–725 µm 2 ). The cell areas of the HMVEC monolayers have larger values, with means above 800 µm 2 (Figure 4A,B).…”
Section: Resultsmentioning
confidence: 99%